SELF-CONCEPT AS A PREDICTOR VARIABLE OF PRIMARY SCHOOL PUPILS’ ACADEMIC PERFORMANCE IN KEBBI STATE - N., Kamba I. M. (Sokoto Educational Review, 2020)
The main thrust of this paper was to find out how self-concept predicts academic performance of primary school pupils in Kebbi State. Pearson product moment correlation coefficient (r) was used to test the hypotheses and the instruments used were Federal Ministry of Education Personality Inventory for Nigerian Junior Secondary School s e lf concept scale and a constructed Mathematics and English languages tests. The finding was that, there is significant relationship between se lf concept and academic performance of primary school pupils. It was therefore, recommended that since there was significant relationship between self-concept and academic performance, teachers and parents should endeavour to train their pupils to have positive self-concept, through praises and encouragements on every effort they make.